Noodleheads lucky day - Arnold, Tedd; Hamilton, Martha; Weiss, Mitch, 1951- (2020)
"Brothers Mac and Mac are SO lucky that everything goes well - even when their frenemy Meatball plays tricks on them"--
Ages 6-9.
Grades 2-3.
Keywords: Graphic novels; Fools and jesters -- Fiction; Luck -- Fiction; Brothers -- Fiction; Humorous stories; Graphic novels